2010
DOI: 10.1159/000321033
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hemodialyzed Patients with Sunitinib in Renal Cell Carcinoma

Abstract: Background: Understanding the effect of adverse events from commonly used agents such as sunitinib in hemodialyzed renal cell carcinoma (RCC) patients is important in clinical practice. Despite its clinical relevance, little information has been provided on the safety and toxicity profile of sunitinib when administered in hemodialyzed patients with RCC. Methods: Six patients undergoing hemodialysis were treated with sunitinib for metastatic RCC between February 2007 and May 2009. We retrospectively reviewed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…In the past, cytokine regimens with interferon (IFN) α-2a and interleukin-2 have been the primary treatment for mRCC. However, newly developed targeted agents have recently replaced the cytokine regimen in the initial treatment for advanced RCC [1,2]. Currently, six targeted agents have been approved for the treatment of mRCC, all of which showed efficacy and tolerable safety in large phase III clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, cytokine regimens with interferon (IFN) α-2a and interleukin-2 have been the primary treatment for mRCC. However, newly developed targeted agents have recently replaced the cytokine regimen in the initial treatment for advanced RCC [1,2]. Currently, six targeted agents have been approved for the treatment of mRCC, all of which showed efficacy and tolerable safety in large phase III clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Although the prevalence of RCC among patients with hemodialysis is 40–100 times higher than the general population,18 the use of sunitinib in dialysis patients is poorly described. Studies based on the limited number of patients seem to suggest that concomitant use of sunitinib and dialysis is feasible with good results 1921. Furthermore, it was suggested that hemodialysis did not significantly alter plasma concentrations of sunitinib 2224.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, cytokine regimens with interferon-α 2a and interleukin-2 have been the primary treatment for metastatic RCC. However, newly developed targeted agents have recently replaced the cytokine regimen in the initial treatment for advanced RCC [4,5,6]. Pazopanib was approved by the US Food and Drug Administration in October 2009 and by the European Medicines Agency in June 2010 for the treatment of metastatic RCC.…”
Section: Introductionmentioning
confidence: 99%